2011
DOI: 10.1530/eje-11-0548
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of hyperthyroidism in Sweden

Abstract: Introduction: The incidence of hyperthyroidism has been reported in various countries to be 23-93/100 000 inhabitants per year. This extended study has evaluated the incidence for w40% of the Swedish population of 9 million inhabitants. Sweden is considered to be iodine sufficient country. Methods: All patients including children, who were newly diagnosed with overt hyperthyroidism in the years [2003][2004][2005], were prospectively registered in a multicenter study. The inclusion criteria are as follows: clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
138
2
12

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 200 publications
(159 citation statements)
references
References 36 publications
(47 reference statements)
7
138
2
12
Order By: Relevance
“…This study is strengthened by the recruitment method that ensures that patients from every clinic in a defined area and population would be recorded. Although this was not an epidemiological study, the incidence was in accordance with previous Swedish incidence studies (34,35,36). Thus, we probably have included almost all eligible subjects and only a small proportion of the patients chose to opt-out from participation.…”
Section: Discussionmentioning
confidence: 69%
“…This study is strengthened by the recruitment method that ensures that patients from every clinic in a defined area and population would be recorded. Although this was not an epidemiological study, the incidence was in accordance with previous Swedish incidence studies (34,35,36). Thus, we probably have included almost all eligible subjects and only a small proportion of the patients chose to opt-out from participation.…”
Section: Discussionmentioning
confidence: 69%
“…A study conducted in Sweden based on the registry of a Swedish Multicenter Study found that 20% of patients with GD had orbitopathy, with 4.9% having infiltrative signs and/ or symptoms and 15.2% having non-infiltrative symptoms (31). In that study, there were geographic differences in the incidence of GD.…”
Section: Clinical Presentationmentioning
confidence: 86%
“…2 TED has an incidence of 42 per million per year. 3 Thyroid eye disease is the most common cause of unilateral and bilateral proptosis ( Figure-1). …”
Section: Introductionmentioning
confidence: 99%